2003
DOI: 10.1046/j.1471-4159.2003.01803.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to kainate‐induced seizures under dietary zinc deficiency

Abstract: Zinc homeostasis in the brain is altered by dietary zinc deficiency, and its alteration may be associated with the etiology and manifestation of epileptic seizures. In the present study, susceptibility to kainate-induced seizures was enhanced in mice fed a zinc-deficient diet for 4 weeks. When Timm's stain was performed to estimate zinc concentrations in synaptic vesicles, Timm's stain in the brain was attenuated in the zincdeficient mice. In rats fed the zinc-deficient diet for 4 weeks, susceptibility to kain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 31 publications
5
65
0
Order By: Relevance
“…The results that the ZnEDTA-treated group exhibited no significant difference to the saline-treated group also supports this hypothesis. Furthermore, it has been reported that zinc transporter-3 (zincT-3)-null mice, which lack histochemically reactive zinc in synaptic vesicles, or zincdeficient mice are more sensitive to seizures induced with kainate (27,28). These reports also imply that vesicular zinc may exert an inhibitive effect on hyperexcitation.…”
Section: +mentioning
confidence: 99%
“…The results that the ZnEDTA-treated group exhibited no significant difference to the saline-treated group also supports this hypothesis. Furthermore, it has been reported that zinc transporter-3 (zincT-3)-null mice, which lack histochemically reactive zinc in synaptic vesicles, or zincdeficient mice are more sensitive to seizures induced with kainate (27,28). These reports also imply that vesicular zinc may exert an inhibitive effect on hyperexcitation.…”
Section: +mentioning
confidence: 99%
“…A decreased T-cell number and altered responses of T-lymphocytes to phytomitogens are indicators of a zinc deficiency in the immune system (Allen et al, 1983;Beck et al, 1997;Bao et al, 2003). Endogenous zinc appears to modulate GABA-mediated synaptic transmission and can block Ca qq channels at Unauthenticated Download Date | 5/9/18 8:28 PM the presynaptic level, causing inhibition of neurotransmitter release (Winegar and Lansman, 1990;Harrison and Gibbons, 1994;Takeda et al, 2003).…”
Section: The Role Of the Essential Trace Element Zinc In Metabolismmentioning
confidence: 99%
“…Depending on the animal model, the receptor type and subunit configuration, zinc can act as a pro-or anticonvulsant agent (32)(33)(34)(35). In animal models of temporal lobe epilepsy, however, zinc seems to decrease seizure activity (34)(35)(36). …”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking vesicular zinc and dietary zincdeficient rats are not only more susceptible to kainic acid-induced seizures, but also have a higher degree of neuronal injury in the hippocampus (34,35). Whether the neuroprotective effects of zinc derive from a reduced release of glutamate or an increase in the concentration of GABA remains elusive, since both mechanisms have been demonstrated in microdialysis studies (37)(38)(39).…”
Section: A B D Cmentioning
confidence: 99%